The Genotype and Phenotype of Proline-Rich Transmembrane Protein 2 Associated Disorders in Chinese Children - Luo, Han-yu; Xie, Ling-ling; Hong, Si-qi; Li, Xiu-juan; Li, Mei; Hu, Yue; Ma, Jian-nan; Wu, Peng; Zhong, Min; Cheng, Min; Li, Ting-song; Jiang, Li (Frontiers in Pediatrics, 2021)
Objectives: To study the genetic and clinical characteristics of Chinese children with pathogenic proline-rich transmembrane protein 2 (PRRT2) gene-associated disorders. Methods: Targeted next generation sequencing (NGS) was used to identify pathogenic PRRT2 variations in Chinese children with epilepsy and/or kinesigenic dyskinesia. Patients with confirmed PRRT2-associated disorders were monitored and their clinical data were analyzed. Results: Forty-four patients with pathogenic PRRT2 variants were recruited. Thirty-five of them (79.5%) had heterozygous mutations, including 30 frameshifts, three missenses, one nonsense, and one splice site variant. The c.649dupC was the most common variant (56.8%). Eight patients (18.2%) showed whole gene deletions, and one patient (2.3%) had 16p11.2 microdeletion. Thirty-four cases (97.1%) were inherited and one case (2.9%) was de novo. Forty patients were diagnosed with benign familial infantile epilepsy (BFIE), two patients had paroxysmal kinesigenic dyskinesia (PKD) and two had infantile convulsions and choreoathetosis (ICCA). Patients with whole gene deletions had a later remission than patients with heterozygous mutations (13.9 vs 7.1 months, P = 0.001). Forty-two patients were treated with antiseizure medications (ASMs). At last follow-up, 35 patients, including one who did not receive therapy, were asymptomatic, and one patient without ASMs died of status epilepticus at 12 months of age. One patient developed autism, and one patient showed mild developmental delay/intellectual disability. Conclusion: Our data suggested that patients with whole gene deletions could have more severe manifestations in PRRT2-associated disorders. Conventional ASMs, especially Oxcarbazepine, showed a good treatment response.